New steps in musical meaning: the metaphoric process as an organizing principle - Jungaberle, Henrik; Verres, Rolf; DuBois, Fletcher (Nordisk tidsskrift for musikkterapi, 2001)
Cognitive metaphor theory provides music psychology and music therapy with some principles for an explanation of musical experience. This is described as personal meaning generation on different levels of information processing. The listeners or players actively merge internal and external contexts with their inframusical, acoustical perceptions. We introduce the concept of “musical scenes” as a characterisation of such contexts in music playing and listening, Here metaphor theory is demonstrated as an empirically based approach that gives insight into some meaning generation processes. Examples are given from interviews with music therapy clients. Finally some ideas on the development of music therapy theory are presented.